MENANAMKAN NILAI-NILAI KARAKTER BERPOLA PEMBIASAAN PERILAKU DI TAMAN KANAK- KANAK ROSIHAN ANWAR - Ashar - Ashar; Sadaruddin - Sadaruddin (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2019)
The purpose of this study is to inculcate character values based on patterns of habitualizing behavior in early childhood, so that they can contribute actively behaving in positive activities that are fun in raising the character values. This research method is to describe the condition of "what is" in an inculcation of character values, so this research uses a descriptive qualitative approach. Therefore, the data analysis technique used in this research is descriptive analysis, data obtained from interviews, observations, documentation, followed by describing, analyzing and interpreting in depth especially data relating to the inculcation of character values patterned in habitual behavior in kindergartens - Kid. To analyze the data begins data reduction, data display, conclusions and verification. Furthermore the validity of the data to obtain the level of confidence in the truth of the results of research. The results of the study Habit positive behavior based on what is seen, heard and felt by students to be emulated in everyday life, so that habituation is carried out in the family environment and school environment (kindergarten). If positive behavior is ingrained in children from an early age, then the students will find it difficult to change their habits so they can get used to behaving wherever the child goes. Behavior habits are inherent in children of course children have automatic behaviors without thinking too much consideration for positive behavior. Application of character values to the pattern of habitual behavior in kindergarten which is an effort to instill the values of religious character, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love of the motherland, respect for achievement friendly, care about the environment, care about social, responsibility. All of these character values require a process and collaboration on the elements that are related between the family, educators and the community to jointly stimulate the child's developmental abilities.